2002
DOI: 10.1097/01.mp.0000021006.53593.b0
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Thymus and Activation Regulated Chemokine and Its Receptor CCR4 in Nodal and Cutaneous Anaplastic Large-Cell Lymphomas and Hodgkin’s Disease

Abstract: Recent studies demonstrated that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 23 publications
5
19
0
Order By: Relevance
“…3, A-E), indicating that T-cell leukemia/lymphoma frequently express CCR4. This finding coincides well with recent reports (23,(25)(26)(27).…”
Section: T-cell Lymphoma and Leukemia Cell Lines Frequently Expressinsupporting
confidence: 83%
See 1 more Smart Citation
“…3, A-E), indicating that T-cell leukemia/lymphoma frequently express CCR4. This finding coincides well with recent reports (23,(25)(26)(27).…”
Section: T-cell Lymphoma and Leukemia Cell Lines Frequently Expressinsupporting
confidence: 83%
“…Inter-estingly, their data demonstrated for the first time that the CCR4 expression correlates with poor prognosis. With respect to other T-cell malignancies, anaplastic large-cell lymphoma (25,26), mycosis fungoides in transformation (25,27), and cutaneous T-cell lymphoma (27) have been observed for the frequent expression of CCR4.…”
Section: Introductionmentioning
confidence: 99%
“…HRS cells produce high levels of TARC and MDC, which are chemoattractants for CCR4, and could play an active role in the influx of CCR4 þ T lymphocytes. 2 Although some controversy exists about the presence of CCR4-positive cells immediately surrounding HRS cells in cHL, 16,32 our results showed significantly higher mRNA level of CCR4 for CD4 þ CD26À T cells and CCR4-positive cells are indeed located in close vicinity to HRS cells. Since Mariani et al 33 showed rapid and efficient CCR4 internalization by MDC but not by TARC, the controversy is probably due to CCR4 internalization by binding to its ligand MDC, which is also highly expressed by HRS cells.…”
Section: -25supporting
confidence: 52%
“…To our knowledge, no other investigators, including Vermeer et al, 24 have previously reported the expression of CCR4 by HL tumor cells from patients ex vivo. On the other hand, some groups have already reported that certain HL cell lines do express CCR4, 23,25 as confirmed in this study.…”
Section: Discussionmentioning
confidence: 99%